Personality Traits as Predictors of Guidance Counsellorsâ€™ Job Performance in Bayelsa State, Nigeria - Edobor, Odiase Jerry; Fred, E. Geoffrey (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The study is centered on personality traits as predictors of guidance counsellorsâ€™ job performance in Bayelsa State. The study was guided by six research questions and six hypotheses. The correlational research design was adopted. A sample of 226 guidance counsellors in government owned secondary schools was drawn from the population, using simple random sampling. Two instruments: â€œThe big five personality Assessment Scaleâ€ (BFPAS)â€ and â€œCounsellor Job Performance Scale (CJPS) were used for data collection. Multiple regression and ANOVA were used to answer the research questions and analyze the hypotheses. The study found out that Big Five personality traits jointly predicts counsellors â€™ job performance. It also found out that neuroticism does not significantly predict counsellor job performance in Bayelsa State. From the findings, the researchers recommended that counsellors should strive to positively channel their personality dispositions towards greater job performance. Also , school administrators should take cognizance of the personality traits of a counsellor before employing and redeploying them. Keywords: Personality traits, Guidance counsellors, Job Performance, Dispositions, and Bayelsa State.